2022
DOI: 10.1002/adfm.202202227
|View full text |Cite
|
Sign up to set email alerts
|

Supported Sub‐Nanometer Clusters for Electrocatalysis Applications

Abstract: Single-atom catalysts (SACs) have attracted great attention in the field of electrocatalysis due to their exceptional activity, selectivity, 100% atom utilization, and tailorability of active sites at atomic level. The metal-support interactions and interatomic synergies, however, are severely limited due to the isolation of active sites in SACs which hinder their applications in some complex reactions. To this end, supported sub-nanometer cluster catalysts (SNCCs, <2 nm) with nearly fully exposed active atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 125 publications
(203 reference statements)
1
16
0
Order By: Relevance
“…[12][13][14][15][16] Recent studies have demonstrated that supported sub-nanometer cluster catalysts (SNCCs) (<2 nm) can exhibit enhanced catalytic performance due to their unique geometric and electronic structure as well as synergistic effect among the atoms within the clusters. [17][18][19][20] The supported SNCCs also exhibit high atom utilization efficiency and can expose much more active atoms than corresponding nanoparticles in catalytic reactions. Meanwhile, compared with singleatom catalysts with uniformly isolated catalytic sites, the supported SNCCs can provide abundant active sites for the adsorption and activation of different intermediates.…”
Section: Doi: 101002/aenm202202913mentioning
confidence: 99%
“…[12][13][14][15][16] Recent studies have demonstrated that supported sub-nanometer cluster catalysts (SNCCs) (<2 nm) can exhibit enhanced catalytic performance due to their unique geometric and electronic structure as well as synergistic effect among the atoms within the clusters. [17][18][19][20] The supported SNCCs also exhibit high atom utilization efficiency and can expose much more active atoms than corresponding nanoparticles in catalytic reactions. Meanwhile, compared with singleatom catalysts with uniformly isolated catalytic sites, the supported SNCCs can provide abundant active sites for the adsorption and activation of different intermediates.…”
Section: Doi: 101002/aenm202202913mentioning
confidence: 99%
“…[48][49][50][51] Note that there are rare reviews on the MNCs and MNCs with different supports for HER, despite there being numerous reports about the MNCs as HER catalysts and some summaries for the nano-metric electrocatalysts recently. [52][53][54] This review, therefore, showcased recent advances in the activity-enhancing strategies of MNCs electrocatalysts, as well as the coordination and support-anchoring strategies. The organic-based structure, metal-based materials, and carbon matrix are systematically discussed as good and usually-used supports.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the utilization efficiency, through the design of single atoms, [12–19] clusters, [20, 21] and specific morphologies [22–24] of Pt‐based catalysts, is a valid approach for reducing the cost of the developed electrocatalysts. Compared with nanoparticles and single atoms, [25–28] sub‐nanometer clusters could expose enough sites and enhance the specific performance simultaneously [29–32] . For instance, Baek and co‐authors [33] found that the Sn nanoclusters in nitrogen‐doped carbon polyhedra (Sn x NC) surpassed the electrocatalytic performance of Sn single atom catalyst for acidic oxygen reduction reaction, owing to the favorable oxygen species adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with nanoparticles and single atoms, [25][26][27][28] sub-nanometer clusters could expose enough sites and enhance the specific performance simultaneously. [29][30][31][32] For instance, Baek and co-authors [33] found that the Sn nanoclusters in nitrogen-doped carbon polyhedra (Sn x NC) surpassed the electrocatalytic perform-ance of Sn single atom catalyst for acidic oxygen reduction reaction, owing to the favorable oxygen species adsorption. Therefore, designing Pt-based electrocatalyst with sub-nanometer size would boost the reaction kinetics and achieve unexpected catalytic performance.…”
Section: Introductionmentioning
confidence: 99%